A STUDY ON COSUMER SATISFACTION TOWARDS THE SALES PROMOTION TECHNIQUES IN KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Sales promotion techniques are essential for businesses to stimulate immediate consumer demand and drive sales in a competitive marketplace. In an environment where consumers are bombarded with options, promotions help a brand stand out and attract attention. For instance, limited-time discounts or flash sales create a sense of urgency, encouraging consumers to act quickly. Promotions also play a critical role in clearing inventory, introducing new products, and generating short-term revenue boosts. Without such strategies, businesses may struggle to maintain consumer interest and sustain growth. Additionally, sales promotion techniques are vital for fostering consumer loyalty and engagement. Programs such as loyalty rewards or referral incentives incentivize repeat purchases, turning one-time buyers into long-term patrons. These techniques also provide businesses with an opportunity to interact directly with their consumers, gaining valuable insights into consumer preferences and behavior. By tailoring promotions to meet specific consumer needs, businesses can enhance consumer satisfaction and build lasting relationships. The important objective of the study is analyzing the consumer satisfaction towards sales promotion techniques in Kanyakumari district. For the above purpose 50 consumers of FMCGs in Kanyakumari district are selected as samples by adopting convenient sampling method.